2017
DOI: 10.1049/iet-epa.2016.0552
|View full text |Cite
|
Sign up to set email alerts
|

MPC to optimise performance in power‐assisted manipulation of industrial objects

Abstract: A 1-DOF power-assist robotic system (PARS) is developed using a linear actuator for vertical manipulation of heavy objects in collaboration with its human user. Human's differential perception of inertia and gravity is considered in the manipulation dynamics, and an admittance-type feedback position control scheme is designed to control the motion of the system. A human manipulates a heavy object with the robot in harmonic motion (the object is repeatedly lifted up and lowered down). A common performance index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…For multi-DoF manipulation, m 1 , m 2 , and G may be customized for each axis of manipulation. 35 The parameters of the VACA in equation (10) and in Figure 11 should be estimated properly and be as much general as possible, but it is better to customize them properly for each particular application (e.g. each object group, subject group, and unimanual/bimanual manipulation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For multi-DoF manipulation, m 1 , m 2 , and G may be customized for each axis of manipulation. 35 The parameters of the VACA in equation (10) and in Figure 11 should be estimated properly and be as much general as possible, but it is better to customize them properly for each particular application (e.g. each object group, subject group, and unimanual/bimanual manipulation).…”
Section: Discussionmentioning
confidence: 99%
“…For multi-DoF manipulation, m 1 , m 2 , and G may be customized for each axis of manipulation. 35…”
Section: Discussionmentioning
confidence: 99%
“…We formulated an MPC taking theoretical and conceptual inspiration from Rawlings and Mayne 36 and Kouvaritakis and Cannon 37 and practical inspiration from Rahman and Ikeura 29 and Rahman et al 35 for the PARS, as shown Figure 10. Mean (n ¼ 10) workload rating scores (out of 100) with standard deviations for the six dimensions of the NASA TLX for the FAC with lightweight and heavy object manipulation.…”
Section: Model Predictive Controlmentioning
confidence: 99%
“…27,28 We call this intuitive and natural HRI and performance calibration approach . Our experience suggests that human-centered intelligent controls such as model predictive control (MPC) 29 and VAC 9 can be two good tools to tune this calibration. However, such approach has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…There are also some problems in the practical applications of PMSM, especially in the aspect of electrifying control based on trajectory planning. At present, the trajectory planning research has been quite mature in the field of robotics, and point-to-point (PTP) motion has a wide range of applications as a common movement [27][28][29]. In the actual electrifying control experiment, electromagnetic torque is very important for the motor.…”
Section: Introductionmentioning
confidence: 99%